Curing studies of bisphenol a based bismaleimide and cloisite 15a nanoclay blends using differential scanning calorimetry and model‐free kinetics. Issue 1 (13th July 2012) - Surender, R.; Mahendran, A.; Thamaraichelvan, A.; Alam, S.; Vijayakumar, C. T.
Abstract Blends of 2, 2‐bis[4‐(4‐maleimidophenoxy phenyl)]propane [bismaleimide (BMIX)] with different proportions (1, 2, 3, 4, 5, 7, and 9%) of the nanoclay Cloisite 15a were prepared with ultrasonication. Fourier transform infrared studies reveal the existence of interactions between the clay particles and the imide rings in BMIX. The difference in the melting characteristics and the decrease in the curing window caused by the incorporation of the clay particles in BMIX, as evidenced by detailed differential scanning calorimetry investigations, confirmed the existence of interactions between the nanoclay particles and BMIX molecules. The Flynn–Wall–Ozawa, Vyazovkin, and Friedman kinetics methods were used to calculate the activation energies (Ea's) for the curing of the BMIX materials. Ea for the polymerization varied, depending not only on the amount of clay loaded in the BMIX but also on the extent of the curing reaction. Because of the loss of interaction between the clay platelets and the imide rings of BMIX, a decrease in Ea at higher reaction extents was noted when there was lower clay loadings (1–4% Cloisite 15a) in BMIX. A reversal in the previous behavior was noted at higher clay loadings (7 and 9% Cloisite 15a) in BMIX and was attributed to the restriction of the molecular mobility due to the presence of increased concentrations of clay platelets and the decreased availability of reaction sites for polymerization. These two opposing factors played were equal at the optimum level of Cloisite 15a loading (5%) in BMIX, which was reflected in the constancy of Ea variation noted with increasing reaction extent. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013